2014
DOI: 10.1111/add.12784
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion interventions and policies addressing excessive alcohol use: a systematic review of national and global evidence as a guide to health‐care reform in China

Abstract: Aims Steady increases in alcohol consumption and related problems are likely to accompany China's rapid epidemiologic transition and profit-based marketing activities. We reviewed research on health promotion interventions and policies to address excessive drinking and to guide health-care reform. Methods We searched in Chinese and English language databases and included 21 studies in China published between 1980 and 2013 that covered each policy area from the WHO Global Strategy to Reduce the Harmful Use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…China has implemented several changes in alcohol taxes, for general economic reasons, and these have been linked to changes in both consumption and alcohol-associated harm 99 . These policy approaches could reduce the burden of ALD, but a recent review reported a dearth of alcohol policy research in China 100 . An increase in alcohol tax in Taiwan in 2002 reduced hospital expenditures on ALD 101 .…”
Section: Treatment Of Audmentioning
confidence: 99%
“…China has implemented several changes in alcohol taxes, for general economic reasons, and these have been linked to changes in both consumption and alcohol-associated harm 99 . These policy approaches could reduce the burden of ALD, but a recent review reported a dearth of alcohol policy research in China 100 . An increase in alcohol tax in Taiwan in 2002 reduced hospital expenditures on ALD 101 .…”
Section: Treatment Of Audmentioning
confidence: 99%
“…Efforts are under way to improve the quality of alcohol‐related primary care, including implementing preventive screening and brief intervention as well as engaging patients in care for alcohol use disorders (AUD) . As these efforts proceed, health systems need practical, valid approaches to measuring changes in patients’ drinking over time in response to interventions .…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use has increased dramatically in China since the 1980s, along with the country’s rapid economic growth (Li et al, 2015). Unlike in many developed countries where alcohol consumption showed a declining trend, China’s per capita alcohol use increased from 2.5L in 1978 to 6.7L in 2010 (Jiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%